Identifying key factors in the mammography procedure for delineating the pectoral muscle using the analytic hierarchy process - Ayako Yagahara; Akari Yoshida (Scientific Reports)
Abstract The quality of mammograms relies on the experience and intuition of radiological technologists, and it takes considerable time to develop the necessary technical skills. The purpose of this study, as a pilot for educational support and improvement in imaging techniques, is to quantitatively elucidate the relationship between the imaging procedure and the delineation of the greater pectoral muscle in the mediolateral oblique view using the Analytic Hierarchy Process (AHP). A questionnaire survey was conducted with six radiological technologists with more than 10 years of clinical experience in mammography examinations. To improve the depiction of the greater pectoral muscle in retakes, whether they are excessively or insufficiently depicted, a questionnaire was created. This questionnaire asked respondents to use a pairwise comparison method to select from among six processes related to muscle depiction. Respondents with a consistency index of 0.2 or below were analyzed, and the importance of each process was calculated. In cases where the great pectoral muscle was excessively depicted, the importance of “positioning the axillary tail to align with the corner of the detector” had the highest value at 0.342. However, in cases where it was inadequately depicted, “adjusting the angle of the detector” was the highest at 0.264, followed by “relaxing the upper body” at 0.247. By using the AHP, the importance in decision-making by experts can be quantified, and these results will greatly contribute to the improvement of technologists’ techniques.